ALIH AKSARA DAN ALIH BAHASA TEKS KITAB MENERANGKAN PERKEMBANGAN AGAMA ISLAM DI MINANGKABAU SEMENJAK DAHULU DARI SYEKH BURHANUDDIN SAMPAI KE ZAMAN KITA SEKARANG - Susilawati, Sri; Hasanuddin WS, Hasanuddin WS; Nurizzati, Nurizzati (Universitas Negeri Padang, 2014)
The aims of this article: (1) presents the results transliteration Text Kitab Menerangkan Perkembangan Agama Islam di Minangkabau Semenjak Dahulu dari Syekh Burhanuddin sampai ke Zaman Kita Sekarang and (2) presents the results of interpretation Text Kitab Menerangkan Perkembangan Agama Islam di Minangkabau Semenjak Dahulu dari Syekh Burhanuddin sampai ke Zaman Kita Sekarang. Object this article is the text of the manuscript Kitab Menerangkan Perkembangan Agama Islam di Minangkabau Semenjak Dahulu dari Syekh Burhanuddin sampai ke Zaman Kita Sekarang. The method used in this article tailored to the stage of research. At this stage of the data collection methods used literature study and field study methods. At this stage of the description text used descriptive method. At this stage of transliteration used transliteration method. At this stage of the language rather than the language used method. The results of this study is to present a text that can be read by the public on the development of contemporary Islam by Shaikh Burhanuddin brought to Minangkabau from the past and present. In this manuscript, there is a vocabulary that shows variance Malay and Minangkabau language in the presentation of the text is maintained. It is intended that the purity of the language contained in the manuscript is maintained.